(untitled) (ESMAT Magazine, 2019)
This work doesn’t intend to exhaust the analysis over the debate or the discussion about the presented theme. On the contrary, it is expected that this work will promote future and broader debates around it, considering the importance, the dimension and the comprehensiveness that issues such as human rights, family and poverty arise nowadays. Thus, in the present text, issues related to freedom for the constitution of the family, where marriage, as one of the main forms for this constitution, deserve particular attention, but also the union of fact, as well as the main institutional guarantees of protection that the Constitution of the Republic of Cape Verde reserves for the family and its members. In the initial part of the text sociodemographic aspects on Cape Verde are presented, within a brief framework. Finally, the realization of social rights, following the institutional guarantees for the protection of the family and its members, as specific tasks attributed to the State and society, in general, by the Constitution of the Republic. In this regard, the right to education, as one of the most effective means of addressing poverty with a view to its reduction / eradication, as well as the public policies adopted by successive governments for the sector are examined.